Serological Evidence of Yersiniosis, Tick-Borne Encephalitis, West Nile, Hepatitis E, Crimean-Congo Hemorrhagic Fever, Lyme Borreliosis, and Brucellosis in Febrile Patients Presenting at Diverse Hospitals in Kenya - Nyataya, Josphat; Maraka, Moureen; Lemtudo, Allan; Masakhwe, Clement; Mutai, Beth; Njaanake, Kariuki; Estambale, Benson B.; Nyakoe, Nancy; Siangla, Joram; Waitumbi, John Njenga (Mary Ann Liebert, Inc. Publishers, 2020)
Data on pathogen prevalence is crucial for informing exposure and disease risk. We evaluated serological evidence of tick-borne encephalitis (TBE), West Nile (WN), Hepatitis E virus (HEV), Crimean-Congo Hemorrhagic Fever (CCHF), Yersiniosis, Lyme Disease (LD), and brucellosis in 1033 patients presenting with acute febrile illness at 9 health care facilities from diverse ecological zones of Kenya: arid and semiarid (Garissa District Hospital, Lodwar District Hospital, Marigat District Hospital, Gilgil District Hospital), Lake Victoria basin (Kisumu District Hospital, Alupe District Hospital, Kombewa Sub-County Hospital), Kisii highland (Kisii District Hospital), and coastal (Malindi District Hospital). Epidemiological information of the patients such as geography, age, gender, and keeping animals were analyzed as potential risk factors. Of the 1033 samples, 619 (59.9%) were seropositive to at least one pathogen by IgM (current exposure), IgG/IgM (recent exposure), and IgG (past exposure). Collective seroprevalence for current, recent, and past to the pathogens was 9.4%, 5.1%, and 21.1% for LD; 3.6%, 0.5%, and 12.4% for WN; 0.9%, 0.5%, and 16.9% for HEV; 5.8%, 1.3%, and 3.9% for brucellosis; 5.7%, 0.2%, and 2.3% for yersiniosis; 1.7%, 0%, and 6.2% for TBE; and 0.4%, 0%, and 1.9% for CCHF. Brucellosis risk was higher in patients recruited at Garissa District Hospital (odds ratio [OR] = 3.41), HEV (OR = 2.45) and CCHF (OR = 5.46) in Lodwar District Hospital, LD in Alupe District Hospital (OR = 5.73), Kombewa Sub-district hospital (OR = 8.17), and Malindi District hospital (OR = 3.3). Exposure to LD was highest in the younger age group, whereas yersiniosis did not vary with age. Age was a significant risk for WN, brucellosis, CCHF, TBE, and HEV and in those aged >14 years there was an increased risk to WN (OR = 2.30, p < 0.0001), brucellosis (OR = 1.84, p = 0.005), CCHF (OR = 4.35, p = 0.001), TBE (OR = 2.78, p < 0.0001), and HEV (OR = 1.94, p = 0.0001). We conclude that LD is pervasive and constitutes a significant health burden to the study population, whereas yersiniosis and CCHF are not significant threats. Going forward, community-based studies will be needed to capture the true seroprevalence rates and the associated risk factors.
Keywords: Yersiniasis; Tick-borne encephalitis; West Nile; Crimean-Congo hemorrhagic fever; Lyne borreliosis; Brucellosis